Gestational Age at Birth and Risk of Developmental Delay: The Upstate KIDS Study - Hochstedler, Kimberly A.; Bell, Griffith; Park, Hyojun; Ghassabian, Akhgar; Bell, Erin M.; Sundaram, Rajeshwari; Grantz, Katherine L.; Yeung, Edwina H. (American Journal of Perinatology, 2020)
Objective The aim of this study is to model the association between gestational age at birth and early child development through 3 years of age.Study Design Development of 5,868 children in Upstate KIDS (New York State; 2008–2014) was assessed at 7 time points using the Ages and Stages Questionnaire (ASQ). The ASQ was implemented using gestational age corrected dates of birth at 4, 8, 12, 18, 24, 30, and 36 months. Whether children were eligible for developmental services from the Early Intervention Program was determined through linkage. Gestational age was based on vital records. Statistical models adjusted for covariates including sociodemographic factors, maternal smoking, and plurality.Results Compared with gestational age of 39 weeks, adjusted odds ratios (aOR) and 95% confidence intervals of failing the ASQ for children delivered at <32, 32–34, 35–36, 37, 38, and 40 weeks of gestational age were 5.32 (3.42–8.28), 2.43 (1.60–3.69), 1.38 (1.00–1.90), 1.37 (0.98–1.90), 1.29 (0.99–1.67), 0.73 (0.55–0.96), and 0.51 (0.32–0.82). Similar risks of being eligible for Early Intervention Program services were observed (aOR: 4.19, 2.10, 1.29, 1.20, 1.01, 1.00 [ref], 0.92, and 0.78 respectively for <32, 32–34, 37, 38, 39 [ref], 40, and 41 weeks).Conclusion Gestational age was inversely associated with developmental delays for all gestational ages. Evidence from our study is potentially informative for low-risk deliveries at 39 weeks, but it is notable that deliveries at 40 weeks exhibited further lower risk.
Keywords: gestational age; developmental delay; preterm; early term